Islamic Education Learning Model in Elementary and Islamic Elementary Schools - Zulhijra Zulhijra; Annisa Ulstami (Universitas Muhammadiyah Enrekang, 2024)
Elementary school-age children in their development have characteristics in terms of thinking, physical, morality, social abilities, and so on. Children's thinking power increases as they get older, and their insight increases, which will make them think concretely, rationally, and objectively, unlike before. In this research, the author applies a qualitative method, a descriptive qualitative approach, and a library study method. Based on this research, it can be said that there are differences in the previous period in the thinking power of elementary school children who have changed from imaginative and egocentric thinking to concrete, rational, and objective thinking. In measuring competency in religious education lessons, you cannot only rely on cognitive assessments but must be complex, namely, cognitive, affective, psychomotor, attitudes, and behavior of students. From the evaluation results, it is hoped that we will create perfect human beings who always try to strengthen their faith, piety, and morals and actively build Islamic civilization.